Analysis of cytochrome b5 reductase-mediated metabolism in the phytopathogenic fungus Zymoseptoria tritici reveals novel functionalities implicated in virulence - Derbyshire, Mark; Michaelson, L.; Parker, J.; Kelly, S.; Thacker, U.; Powers, S.; Bailey, A.; Hammond-Kosack, K.; Courbot, M.; Rudd, J. (Academic Press Inc., 2015)
Septoria tritici blotch (STB) caused by the Ascomycete fungus Zymoseptoria tritici is one of the most economically damaging diseases of wheat worldwide. Z. tritici is currently a major target for agricultural fungicides, especially in temperate regions where it is most prevalent. Many fungicides target electron transfer enzymes because these are often important for cell function. Therefore characterisation of genes encoding such enzymes may be important for the development of novel disease intervention strategies. Microsomal cytochrome b5 reductases (CBRs) are an important family of electron transfer proteins which in eukaryotes are involved in the biosynthesis of fatty acids and complex lipids including sphingolipids and sterols. Unlike the model yeast Saccharomyces cerevisiae which possesses only one microsomal CBR, the fully sequenced genome of Z. tritici bears three possible microsomal CBRs. RNA sequencing analysis revealed that ZtCBR1 is the most highly expressed of these genes under all in vitro and in planta conditions tested, therefore ΔZtCBR1 mutant strains were generated through targeted gene disruption.These strains exhibited delayed disease symptoms on wheat leaves and severely limited asexual sporulation. ΔZtCBR1 strains also exhibited aberrant spore morphology and hyphal growth in vitro. These defects coincided with alterations in fatty acid, sphingolipid and sterol biosynthesis observed through GC–MS and HPLC analyses. Data is presented which suggests that Z. tritici may use ZtCBR1 as an additional electron donor for key steps in ergosterol biosynthesis, one of which is targeted by azole fungicides. Our study reports the first functional characterisation of CBR gene family members in a plant pathogenic filamentous fungus. This also represents the first direct observation of CBR functional ablation impacting upon fungal sterol biosynthesis.